Outer order, inner calm eaudiobook Declutter and organize to make more room for happiness. - Rubin, Gretchen (Random House Audio, 2019)
NEW YORK TIMES  BESTSELLER • In this lovely, easy-to-use illustrated guide to decluttering, the beloved author of  The Happiness Project  shows us how to take control of our  stuff —and, by extension, our lives.   Gretchen Rubin knows firsthand that creating order can make our lives happier, healthier, more productive, and more creative. But for most of us, a rigid, one-size-fits-all solution doesn't work. When we tailor our approach to suit our own particular challenges and habits, we can find inner calm.   With a sense of fun, and a clear idea of what’s realistic for most people, Rubin suggests dozens of manageable tips and tricks for creating a more serene, orderly environment, including:   • Never label anything “miscellaneous.” • Ask yourself, “Do I need more than  one ?” • Don’t aim for minimalism. • Remember: If you can’t retrieve it, you won’t use it. • Stay current with a child’s interests. • Beware the urge to “procrasticlear.”   By getting rid of things we don’t use, don’t need, or don’t love, we free our minds (and our shelves) for what we truly value.